Gender differences in driving under the influence (DUI) program client characteristics: Implications for treatment delivery. Issue 2 (7th February 2019) - Reilly, Kelly; Woodruff, Susan I.; Hohman, Melinda; Barker, Melanie
ABSTRACT: The purpose of this descriptive study was to examine gender differences in the characteristics of clients in a large Driving Under the Influence (DUI) program in Southern California. We analyzed secondary de-identified data from a large DUI program for the years 2009–2014 ( n = 19, 619). Sociodemographic characteristics, measures of physical and mental comorbidity, and alcohol use severity measures were compared for male and female clients. Women averaged 32.85 years of age (SD = 10.70), while men were slightly older at 34.2 years (SD = 11.19). Females comprised an increasingly greater percentage of the client population over the time period studied (27.6%–30.7%). In a multivariable model, compared to male clients, females were more likely to be White non-Hispanic, not currently married, and younger. Women were more likely than men to report anxiety, depression, and a history of domestic violence. Blood alcohol content at arrest and measures of hazardous drinking did not differ significantly by gender. Results suggested that gender-specific DUI programs might be useful.